Stray Currents on Direct – Current Railways in Slovenia - Bojan Cene (Communications - Scientific letters of the University of Zilina, 2009)
DC stray currents are currents which do not flow through designed conductors but along the path of least resistance. These currents are very harmful to various metallic structures and lead to corrosion in the long term. The most significant sources of DC stray currents in Slovenia can be found in electrified railways using the direct current system of 3000 V. Not all the return current can flow back to the rectifier substation through the rails but a high percentage of this current is dispersed in the earth, depending on conductive arteries. In some cases, these stray currents even cross a very winding railway line.The Slovenian Railways have electrified a substantial part of their railway lines using the direct current system of 3000 V. The complete 3000 V direct current overhead line system in Slovenia is being fed by 18 rectifier substations (ENP).